Prioritizing non-vehicular users: a redesign of Franklin Park’s circulation to improve quality and usability - Kalamaja, John V. (Kansas State University, 2023)
Franklin Park, in Boston, Massachusetts, is a 500+-acre urban park designed by renowned landscape architect Fredrick Law Olmsted in the 1880s. A signature feature of Olmsted’s design was the circulation system, which enabled parkgoers to navigate the site’s unique topography through continuous and easily traversed paths (Boston Parks & Recreation Department 2022). However, starting with the introduction of cars into the park in the 1930s, the circulation system has since changed, resulting in an overall experience that is largely fragmented, unsafe, inaccessible, and confusing for non-vehicular users. Yet circulation quality is especially important for usability by non-vehicular users, like cyclists and pedestrians. Thus, this project sought to understand what design criteria matter most for a quality circulation system and how Franklin Park’s circulation system could be redesigned to prioritize non-vehicular users. To address the project’s research question, a multi-step process was developed. The first step involved a literature review to determine the circulation needs of different non-vehicular user groups. Next, a review of existing analysis frameworks was done to determine what design criteria matter most for circulation quality and usability by non-vehicular users. From this, the Quality of Circulation for Non-Vehicular Users framework was developed. The framework includes twenty criteria organized into three categories–comfort, protection, and delight. Next, the framework was used to guide a precedent study of existing circulation systems to identify examples of the twenty criteria. Then, the framework was used to structure a site analysis of Franklin Park’s circulation system to determine where improvements could be made. And finally, findings from the precedent and site analysis informed a projective design of Franklin Park’s circulation system, which sought to improve the overall quality and usability for non-vehicular users through various macro and microscale design improvements. Ultimately, the Quality of Circulation framework was found to be a useful tool for guiding site analysis and informing design changes to improve circulation quality and usability. The framework’s value extends beyond this report as it can be used by landscape architects, planners, and municipalities looking to transform and prioritize the non-vehicular user experience.
Keywords: Non-vehicular transportation; Circulation; Quality criteria; Cycling; Franklin Park